2014
DOI: 10.1111/his.12402
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of subepithelial interstitial cells in normal and pathological human prostate

Abstract: The present study shows for the first time that the SE area in the human prostate houses different stromal cell types with distinct phenotypes. In BPH and PCa specific disease-related changes were observed in the organization and phenotypes of SE interstitial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Wrapping cells are also fibroblast-like, and are tightly associated with the outer part of the smooth muscle layer, whereas interstitial fibroblasts are located between prostate ducts (Peng et al, 2013). In the case of the human prostate, ultrastructural analyses of subepithelial cells have resulted in their subdivision into fibroblasts, interstitial Cajal-like cells and spindle-shaped cells with myoid differentiation (Gevaert et al, 2014). Tissue recombination studies have suggested that the differentiation of smooth muscle cells from the UGM is regulated by signaling from the adjacent epithelium during organogenesis (Hayward et al, 1997).…”
Section: Stromal Progenitors and Differentiation During Prostate Devementioning
confidence: 99%
“…Wrapping cells are also fibroblast-like, and are tightly associated with the outer part of the smooth muscle layer, whereas interstitial fibroblasts are located between prostate ducts (Peng et al, 2013). In the case of the human prostate, ultrastructural analyses of subepithelial cells have resulted in their subdivision into fibroblasts, interstitial Cajal-like cells and spindle-shaped cells with myoid differentiation (Gevaert et al, 2014). Tissue recombination studies have suggested that the differentiation of smooth muscle cells from the UGM is regulated by signaling from the adjacent epithelium during organogenesis (Hayward et al, 1997).…”
Section: Stromal Progenitors and Differentiation During Prostate Devementioning
confidence: 99%
“…Telocytes (TCs) were identified as a new cell type of the stromal space [1] (details at www.telocytes.com). TCs were described in the trachea and lungs [2][3][4][5], besides other important locations: heart [6][7][8][9], female reproductive system [10][11][12][13], skin [14,15], digestive system [16][17][18][19], liver [20], urinary tract [21,22], prostate [23,24], skeletal muscle and neuromuscular spindles [25,26], eye [27], etc. Ultrastructurally, TCs are defined and easily to distinguish by their extremely long telopodes (tens up to hundreds of micrometres), an alternation of podoms and podomeres.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that diverse stromal cell types with distinct phenotypes reside in the subepithelial area in the human prostate . We next explored the exact PD‐L1 + cell type in the TME.…”
Section: Resultsmentioning
confidence: 99%
“…A rabbit monoclonal PD‐L1 antibody (clone E1L3N) was investigated for use in immunohistochemistry (IHC). Markers for stromal cells were previously described to characterize the morphology and phenotype of subepithelial interstitial cells in prostate stroma: Vimentin, α‐SMA, CD34 and pan neuron marker protein gene product 9.5 (PGP9.5) . For tumor‐associated lymphocytes (TALs), we labeled tissue slides for FoxP3, CD3 and CD8 to highlight different lymphocyte subsets, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation